The History of St. Paul's Episcopal Church of Kern County - Metcalf, Maud; Sanford, Louis C.; Bender, Cora; Patrick, William E.; Mangun, Mary E.; Harrell, Alfred; Sanford, Louis C.; Metcalf, Maud
Handwritten and typed manuscripts for a 1934 publication on the history of St. Paul's Episcopal Church, profiles on its clergy, as well as relevant historical information regarding Bakersfield, Kern County and the region.